2020
DOI: 10.3390/su12010356
|View full text |Cite
|
Sign up to set email alerts
|

Motives and Role of Religiosity towards Consumer Purchase Behavior in Western Imported Food Products

Abstract: The undertaken study examines the influence of the marketing mix, consumer attributes, and the role of religiosity towards consumer purchase behavior regarding western imported food products in Pakistan. The study has used the theory of planned behaviors as underpinning foundations for testing factors. In total, 1080 respondents from eight cities in Pakistan—Karachi, Lahore, Islamabad, Quetta, Peshawar, Hyderabad, Larkana, and Faisalabad—were part of this study. Path analysis performed through SEM (structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 85 publications
2
26
0
1
Order By: Relevance
“…Consumers also choose companies that have a reputation as producers of halal products. This is consistent with the results of previous studies Bukhari et al [14] that religiosity is positively correlated with interest in purchasing certain products in Muslim countries.…”
Section: Discussionsupporting
confidence: 93%
“…Consumers also choose companies that have a reputation as producers of halal products. This is consistent with the results of previous studies Bukhari et al [14] that religiosity is positively correlated with interest in purchasing certain products in Muslim countries.…”
Section: Discussionsupporting
confidence: 93%
“…The interest rate is forbidden in Islamic values; therefore, religious belief is fundamental in choosing Islamic ebanking services. Religious belief is a fundamental component for clients who decide on any Islamic banking product (Flores et al, 2020;Bukhari et al, 2020;Dusuki & Abdullah, 2007). Previous literature demonstrated that religious belief is a significant construct in the Islamic ebanking sector (Lodhi, 2020;Ahmed et al, 2019;Haron et al, 1994).…”
Section: Religiositymentioning
confidence: 99%
“…Hasil temuan beberapa kajian sebelumnya menunjukkan bahwa terdapat beberapa aspek yang menentukan pergeseran pola konsumsi individu maupun masyarakat. Pergeseran pola konsumsi tersebut ditentukan oleh tujuan membeli produk (Wang & Chao, 2020;Eisend & Hermann, 2020), kemasan produk yang menarik (Chen et al, 2017;Wijekoon & Sabri, 2021), penampilan dan reputasi (Bilro & Loureiro, 2020), berdasarkan biaya dan bukan berdasarkan manfaat atau kegunaan (Bukhari et al, 2020), status sosial (Boström, 2020), dan kepercayaan diri (White et al, 2019;Pang et al, 2021).…”
Section: Gambar 1 Pertumbuhan Pdrb Provinsi Sulawesi Selatan Menurut Pengeluaranunclassified